Smart low power listening for wireless sensor networks - HU Si-quan1; WANG Jun-feng2 (Tongxin xuebao)
As a representative MAC for wireless sensor networks, low power listening（LPL） used a long preamble in each transmission and caused significant overhearing cost in a dense deployment.To save such cost, a new MAC protocol-smart low power listening（SLPL） was proposed by embedding destination address and preamble index into the ordinary preamble.Both the theoretical analysis and the deployment test show that SLPL outperforms LPL in power efficiency.The test also shows that SLPL saves more power than X-MAC.